Dinamika Beberapa Sifat Fisika Tanah Dibawah Sistem Usahatani Konservasi Pada Lahan Kritis Aripan Di DTA Singkarak - Aprisal Aprisal; Bujang Rusman; Indra Dwipa; Refdinal Refdinal; Erlina Rahmayuni; Fajriwandi Fajriwandi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2016)
Aprisal. et al.Â Dynamics of Some Physical Properties of Soils Under Conservation Farming System on the Critical Land Aripan in the DTA Singkarak. JLSO 5(2):137-144.The conservation farming on critical land can improve the soil properties and maintantain for a periode of time. The purpose of this research is to study the dynamics of critical landâ€™s physical characteristics under the influence of conservation farming at Singkarak Water Catchment Area (DTA) in Nagari Aripan. The analysis of soil sample is conducted in Soil Science Department Laboratory, Faculty of Agriculture, Andalas University. This research is designed with Split Plot Design (RPT). The main plot is a soil processing system which is: conventional soil processing (po), soil processing with mulch (p1), soil processing with compost and manure (p2) and minimum soil processing (p3), while the sub plot consists of three types of plants, they are; sweet corn (t1), soy bean (t2) and peanut (p3). Each treatment is repeated three times. Result of the research is observation data in each season of the first, second and third year. To see the dynamics of soil characteristics, data of each season is viewed through graphic which based on its trend. The result of the research indicates that utilization of critical land with conservation farming system could repair and maintain some physical characteristics of soil in each growing season, such as: decreasing volume, increasing soil organic matter, porosity, and soil permeability. Productivity of soil increases on the conventional processing with mulch, compost, and manure. Conventional soil processing with added compost and manure increases productivity for 32.58% in the first year, 45.16% in the second year, and 59.73% in the third year.